KEBIJAKAN LIBERALISASI FOREIGN PORTFOLIO INVESTMENT DAN IMPLIKASINYA TERHADAP KEBIJAKAN PERBANKAN NASIONAL DALAM PEMBERIAN KREDIT USAHA MIKRO KECIL MENENGAH (UMKM) DI INDONESIA (Periode Megawati Soekarnoputri â Susilo Bambang Yudhoyono) - , Sugeng Ribowo; , Dra. Siti Daulah Khoiriati, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Foreign Portfolio Investment is one of the parts of foreign investment policy, its existence has the important role to the economic development of a country, especially to the developing countries to prevent the deficit of a country. Indonesia is one of developing countries that has implemented the policy rapidly by liberating foreign portfolio investment. This makes the foreign fund flood Indonesia without any control. Its legally caused legislation product regulating the kinds of this investment subtancially do not regulate legal precision between two countries. Therefore, it gives overborrowing impacts that have to be guaranted by a country in a certain time. Its different from other developing countries determined foreign portfolio investment with the strong control and given tax disincentive to the investors, such as China, Corea, Thailand and others. The behavior of this policy, is appereant and it cannot be separate from foreign influence that suggested by International Monetary Fund (IMF) and World Bank (WB) as a financial international institution with the basic financial globalization. Financial globalization, directly and indirectly has supported the government policy that is very kind to the foreign intervention. Its evidenced by the dominated legalize by the ownership of foreign stock in foreign right corporation or financial institution (banking) that has implicitly through laws. Therefore, foreign portfolio investment has caused the magnetic strength, especially banking institution to get the traget of big gain by buying and selling it to foreigner than distributing of credit to the small and medium enterprises. This Phenomenon, implicates to the change to the policy in the banking sector, banking experienced shifting of vital function that as to be able to allocate the fund source to the society efficienly and effectivetely. The shifting of vital banking function, from traditional activity to the non-traditional activity is caused by the complicated problems like institution, regulation, and globalization, especially financial globalization. Therefore, the strength of the state about political economy is the main solution to solve these problems. This research, will be analyzed comprehensively about the Policy of Foreign Portfolio Investment Liberalization and its Implications toward the National Banking Policy on Giving the Credit to the Small and Medium Enterprises. Beside, this research will also be explained the relevant policy to solve the vital functions of banking as intermediation institution to the small and medium enterprises, its influence can be hoped to the financial stability and economic development sustainability.